From Inquilines to Gall Inducers: Genomic Signature of a Life-Style Transition in Synergus Gall Wasps. (28th September 2020) - Gobbo, Erik; Lartillot, Nicolas; Hearn, Jack; Stone, Graham N; Abe, Yoshihisa; Wheat, Christopher W; Ide, Tatsuya; Ronquist, Fredrik
Abstract: Gall wasps (Hymenoptera: Cynipidae) induce complex galls on oaks, roses, and other plants, but the mechanism of gall induction is still unknown. Here, we take a comparative genomic approach to revealing the genetic basis of gall induction. We focus on Synergus itoensis, a species that induces galls inside oak acorns. Previous studies suggested that this species evolved the ability to initiate gall formation recently, as it is deeply nested within the genus Synergus, whose members are mostly inquilines that develop inside the galls of other species. We compared the genome of S. itoensis with that of three related Synergus inquilines to identify genomic changes associated with the origin of gall induction. We used a novel Bayesian selection analysis, which accounts for branch-specific and gene-specific selection effects, to search for signatures of selection in 7, 600 single-copy orthologous genes shared by the four Synergus species. We found that the terminal branch leading to S. itoensis had more genes with a significantly elevated d N /d S ratio (positive signature genes) than the other terminal branches in the tree; the S. itoensis branch also had more genes with a significantly decreased d N /d S ratio. Gene set enrichment analysis showed that the positive signature gene set of S. itoensis, unlike those of the inquiline species, is enriched in several biological process Gene Ontology terms, the most prominent of which is "Ovarian Follicle Cell Development." Our results indicate that the origin of gall induction is associated with distinct genomic changes, and provide a good starting point for further characterization of the genes involved.